Melatonin - Molecular Biology, Clinical and Pharmaceutical Approaches 2018
DOI: 10.5772/intechopen.80005
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin in Childhood Epilepsy and in Child Neurology

Abstract: Melatonin (MLT) was isolated as a hormone by Lerner in 1958, and since then, intense studies have been under way with respect to its action and possibilities of application in various fields of medicine. Despite the existence of multiple antiepileptic medications and progress that has taken place in neurosurgical treatment of epilepsy, drug-resistant epilepsy continues to be a phenomenon that occurs in 30-35% children treated for epileptic seizures. Reports presented in the study have shown that children with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 106 publications
(194 reference statements)
0
5
0
Order By: Relevance
“…Seizures reportedly occur more frequently in phase 2 of NREM (61-68%), phases 3 and 4 of NREM (9-14%), and the REM phase (0-5%). 20 Circadian rhythm is also disorganized in children with epilepsy due to changes in the wake-sleep cycle controlled by the suprachiasmatic nucleus (SCN) in the anterior hypothalamus. Melatonin hormone secretion pattern is disturbed, with high concentrations at night or after a seizure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seizures reportedly occur more frequently in phase 2 of NREM (61-68%), phases 3 and 4 of NREM (9-14%), and the REM phase (0-5%). 20 Circadian rhythm is also disorganized in children with epilepsy due to changes in the wake-sleep cycle controlled by the suprachiasmatic nucleus (SCN) in the anterior hypothalamus. Melatonin hormone secretion pattern is disturbed, with high concentrations at night or after a seizure.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbed melatonin secretion patterns change the wake-sleep cycle and wake-promoting signal of the SCN, thus causing sleep disorders. [20][21] Epilepsy increases sleep onset latency or sleep onset delay, increases the number and duration of wakefulness episodes after sleep onset, decreases sleep efficiency, reduces spindle sleep, and increases REM phase abnormalities. A study in India showed that seizures in children with epilepsy had significant correlations with wake disorders and pathological sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin appears to reduce seizure activity in human investigations of temporal‐lobe epilepsy (Albertson et al., 1981 ; Borowicz et al., 1999 ; Champney et al., 1996 ; de Lima et al., 2005 ; Mevissen & Ebert, 1998 ; Pévet, 2022 ; Rosenstein et al., 1990 ). Melatonin does not appear to have an impact on the normal electroencephalogram (EEG) (Paprocka et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin's anticonvulsant action has been linked to some different pathways. Its antioxidant, antiexcitotoxic, and free radical scavenging activities in the central nervous system (CNS) provide neuroprotection (Goldberg‐Stern et al., 2012 ; Gupta, Gupta, et al., 2004 ; Gupta, Aneja, et al., 2004 ; Gupta et al., 2005 ; Paprocka et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we showed that melatonin secretion in children with hypoxic ischemic encephalopathy (HIE) is significantly disturbed, even stronger than in epilepsy. Its characteristic features, as seen from the blood sampling [ 3 , 4 ], are the delayed melatonin phase release and the shift of the DLMO parameters to the later morning hours.…”
Section: Introductionmentioning
confidence: 99%